2020
DOI: 10.1016/j.ridd.2020.103632
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with autism severity among Malaysian children with Autism Spectrum Disorder

Abstract: Background: Children with Autism Spectrum Disorder (ASD) of different levels of symptom severity may exhibit a wide range of behaviours and characteristics. There is a limited nutritionrelated study on children with ASD of different severity in Malaysia. Aims: This cross-sectional study aims to determine the association between sociodemographic factors, parental factors, and lifestyle factors with autism severity in children with ASD. Methods and procedures: A total of 224 children with ASD were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
2
3
1
Order By: Relevance
“…Contrary to the current study findings, a recent study stated that the father's employment status and perceived child weight were the significant predictors of autism severity and suggested that paternal unemployment might have resulted in higher parental participation in early intervention for their children (Eow, Gan, Lim, Awang, & Mohd Shariff, 2020).…”
Section: Table (5)contrasting
confidence: 99%
“…Contrary to the current study findings, a recent study stated that the father's employment status and perceived child weight were the significant predictors of autism severity and suggested that paternal unemployment might have resulted in higher parental participation in early intervention for their children (Eow, Gan, Lim, Awang, & Mohd Shariff, 2020).…”
Section: Table (5)contrasting
confidence: 99%
“…This current study reported mild and moderate ASD among the respondents. The findings differed from a study by Eow et al (2020), which reported that 78.1% of the Television viewing time, computer time and total screen time were reported to be significantly higher in 3 to 11 years old children with ASD compared to typically developing children in the USA (Must et al, 2014). The higher screen time recorded by autistic children can be because of the use of screen media devices to control the tantrums of autistic children (Dunckley, 2016).…”
Section: Discussioncontrasting
confidence: 71%
“…A Malaysian study regarding feeding practices in children with ASD also found that the majority (94.6%) practiced an authoritarian parenting style. 29 In this study, authoritarian caregiver feeding style was associated with feeding difficulties. Studies have found varying relationships between parental feeding style and child's feeding difficulties.…”
Section: Discussionmentioning
confidence: 60%